Design and synthesis of new spirooxindole candidates and their selenium nanoparticles as potential dual Topo I/II inhibitors, DNA intercalators, and apoptotic inducers - Samar El-Kalyoubi; Mohamed M. Khalifa; Mahmoud T. Abo-Elfadl; Ahmed A. El-Sayed; Ahmed Elkamhawy; Kyeong Lee; Ahmed A. Al-Karmalawy (Journal of Enzyme Inhibition and Medicinal Chemistry, 2023)
A new wave of dual Topo I/II inhibitors was designed and synthesised via the hybridisation of spirooxindoles and pyrimidines. In situ selenium nanoparticles (SeNPs) for some derivatives were synthesised. The targets and the SeNP derivatives were examined for their cytotoxicity towards five cancer cell lines. The inhibitory potencies of the best members against Topo I and Topo II were also assayed besides their DNA intercalation abilities. Compound 7d NPs exhibited the best inhibition against Topo I and Topo II enzymes with IC50 of 0.042 and 1.172 μM, respectively. The ability of compound 7d NPs to arrest the cell cycle and induce apoptosis was investigated. It arrested the cell cycle in the A549 cell at the S phase and prompted apoptosis by 41.02% vs. 23.81% in the control. In silico studies were then performed to study the possible binding interactions between the designed members and the target proteins.